Reducing poverty and hunger through food policy research: Highlights of recent IFPRI research and partnerships with Germany - International Food Policy Research Institute (International Food Policy Research Institute, 2017)
For more than three decades, the International Food Policy Research Institute (IFPRI) has engaged in strong partnerships with German development agencies, universities, and nongovernmental organizations (NGOs) to build the evidence base needed to effectively tackle pressing development issues. Initially, IFPRI and German partners worked together to identify strategies that promote sustainable rural development for reducing poverty; over time, the collaborations have expanded to include food and nutrition security. The German government’s longstanding, generous, and unrestricted support has allowed IFPRI to conduct cutting-edge policy research. IFPRI’s project-specific work with the Federal Ministry for Economic Cooperation and Development (BMZ) and the German Agency for International Cooperation (GIZ) has contributed to global, regional, and national development strategies. Various partnerships between IFPRI and the German government have influenced effective strategies for agricultural growth and building resilience to climate change, particularly in Africa. In addition, IFPRI has worked with prestigious German academic centers and universities, such as the Center for Development Research at the University of Bonn (ZEF) and the University of Hohenheim, as well as with German NGOs, such as Welthungerhilfe, and participated in BMZ’s Postdoctoral Fellowship Program. The result has been an exceptional integration and exchange of knowledge on critical issues related to food and nutrition security, which has enhanced the quality of research as well as the development outcomes and impact of both IFPRI and the German organizations.